Two new subspecies of Cortodera villosa Heyden, 1876 (Coleoptera: Cerambycidae) from South Russia - M.L. Danilevsky (Кавказский энтомологический бюллетень, 2011)
Cortodera villosa kuvandykensis ssp. n. is described from Kuvandyk district in the north of Orenburg region of Russsia. The new subspecies is close to C. v. magdeevi Danilevsky, 2011 from Zhiguli Mts., but differs by small number of light forms in the population and details of elytral pubescence. Cortodera villosa chuvilini ssp. n. is described from south-west part of Volgograd region (Golubinskoe village). It differs from all previously known subspecies of C. villosa by small and wide body with domination of specimens with brown elytra. The taxonomy rank is downgrated for C. parfentjevi Miroshnikov, 2007 and C. zhuravlevi Miroshnikov, 2007: C. villosa parfentjevi Miroshnikov, 2007, stat. n. (Crimea) and C. v. zhuravlevi Miroshnikov, 2007, stat. n. (Orenburg environs and NW Kazakhstan). C. zhuravlevi aktolagaica Miroshnikov, 2007 is accepted as C. villosa aktolagaica Miroshnikov, 2007 (Aktolagay Mts. in West Kazakhatan).